Reporting dental trauma and its inclusion in an injury surveillance system in Victoria, Australia. (March 2015) - Dang, KM; Day, PF; Calache, H; Tham, R; Parashos, P
Abstract Background This study investigated the frequency, patterns and causes of dental trauma in patients seeking emergency treatment at a dental hospital, and evaluated the impact of an electronic structured injury history form to collect key information. Methods A retrospective audit was undertaken of all emergency presentations at the Royal Dental Hospital of Melbourne from 2009 to 2012. Dental trauma and injury surveillance data were collected and evaluated with reference to the criteria of the Victorian Emergency Minimum Dataset. Statistical analysis included chi‐squared and Fisher's exact tests. Results A total of 88 610 new emergency courses of care were created, with 3642 (4.1%) identified as new dental trauma cases in 3574 patients. A total of 6001 teeth were injured with a mean of 1.7 teeth per patient (range: 1–8 teeth). The improvement of injury surveillance information collected using the electronic form compared with the paper form was statistically significant (p < 0.001). Conclusions The dental trauma findings of this study are consistent with other studies regarding age, gender, location, cause and injury type. This study also confirmed the benefits of electronic collection of dental injury surveillance data that can assist policy planners and health service providers in designing and delivering effective dental injury prevention and management services.